A novel empirical approach to measuring pore gas compositional change in mine waste storage facilities: A case study from northern Europe - Schoen, D.; Savage, R.; Pearce, S.; Shiimi, R.; Gersten, B.; Roberts, M.; Barnes, A. (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
The transition to a net-zero economy will place increased demand upon global mine production of key resources, increasing waste generation and life-of-mine (LOM) greenhouse gas emissions. The increased waste generation accompanying this transition will increase the need for sustainable waste management/closure. Pore gas compositions in waste rock facilities are a key control factor on sulfide oxidation and subsequent acid rock drainage (ARD) onset. Understanding pore gas changes in waste facilities post closure is essential to understand long term management risks and feasibility of closure engineering strategies (e.g. covers) to meet long term closure goals. To date no standardised empirical testing method exists to estimate the relative change in pore gases (e.g. O2 and CO2), and long term flux rates of these gases within waste facilities once encapsulation of waste has been undertaken. Silicate weathering and carbonate precipitation provide a key source of alkalinity in low carbonate waste materials and are a key control on acid generation potential. These silicate minerals also provide a potential feedstock for both active and passive carbon capture, through enhanced weathering/mineral carbonation. Previous studies have recorded evidence of both CO2 release and carbon sequestration within waste rock and tailings of several operating and closed sites across the globe, yet the concept remains underdeveloped with regards to policy and standardisation. Understanding the relative rates of sulfide oxidation, silicate weathering, carbonate buffering and pore gas/water geochemical interaction is key in predicting long term pore gas changes in waste rock facilities. This study presents a method of measuring the relative balance between sulfide oxidation, carbonate buffering and silicate mineral carbonation rates of mine wastes using bespoke sealed experimental cells partially filled with sulfidic ultramafic mine waste. Fitted high-accuracy probes within the air space of cells track CO2 and O2 flux, with changes being indicative of processes including carbon sequestration and sulfide oxidation/carbonate buffering. Reported relative gas concentrations are converted to absolute values using known variables in conjunction with the ideal gas law, allowing for estimates to be made regarding CO2 and O2 uptake/release over a given logging period. Variables such as waste type, moisture content, temperature and starting gas composition are modified to simulate various site conditions. This study aims to outline the workings of the measurement method along with displaying its potential as a tool to assess post closure pore gas changes in waste storage facilities.